Building Consumer Satisfaction Through Green Marketing Strategy Analysis on Purchasing Decisions: A Case Study in Jabodetabek - Diana Silaswara; Puti lenggo ginny; Canggih Gumanky Farunik (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
The purpose of this research was to understand consumer behavior regarding the purchase of environmentally friendly products. The respondents selected were those residing in Greater Jakarta (Jabodetabek). However, due to the lack of definitive data on the number of consumers of environmentally friendly products, the researcher used the Hair method to determine the sample size. This was done by multiplying the number of indicators (19) by 10 (a minimum of 190 respondents). This study successfully obtained 194 valid respondents. This research is a deductive-inductive study, using a problem-based approach followed by hypothesis testing. Hypothesis testing is the process of proving cause and effect (influence) between exogenous and endogenous variables using the SEM PLS 3.0 analysis tool to process the questionnaire results. The results of the data show that only variables X1 (Green Product) and X2 (Green Price) have a significant influence in forming Z (Consumer Satisfaction), while X3 (Green Promotion) together with Z (consumer satisfaction) have a greater influence on Y (Purchase Decision) while X1 and X2 do not have a significant influence on Y.